Causes and predictors of unplanned reoperations within 30 days post laparoscopic pancreaticoduodenectomy: a comprehensive analysis - Zhang, Shiwei; Yadav, Dipesh Kumar; Wang, Gaoqing; Jiang, Yin; Zhang, Jie; Yadav, Rajesh Kumar; Singh, Alina; Gao, Guo; Chen, Junyu; Mao, Yefan; Wang, Chengwei; Meng, Yudi; et al. (Frontiers in Oncology, 2024)
Objective To delineate the risk factors and causes of unplanned reoperations within 30 days following laparoscopic pancreaticoduodenectomy (LPD). Methods A retrospective study reviewed 311 LPD patients at Ningbo Medical Center Li Huili Hospital from 2017 to 2024. Demographic and clinical parameters were analyzed using univariate and multivariate analyses, with P < 0.05 indicating statistical significance. Results Out of 311 patients, 23 (7.4%) required unplanned reoperations within 30 days post-LPD, primarily due to postoperative bleeding (82.6%). Other causes included anastomotic leakage, abdominal infection, and afferent loop obstruction. The reoperation intervals varied, with the majority occurring within 0 to 14 days post-surgery. Univariate analysis identified significant risk factors: diabetes, liver cirrhosis, elevated CRP on POD-3 and POD-7, pre-operative serum prealbumin < 0.15 g/L, prolonged operation time, intraoperative bleeding > 120 ml, vascular reconstruction, soft pancreatic texture, and a main pancreatic duct diameter ≤3 mm (all P < 0.05). Multivariate analysis confirmed independent risk factors: pre-operative serum prealbumin < 0.15 g/L (OR = 3.519, 95% CI 1.167-10.613), CRP on POD-7 (OR = 1.013, 95% CI 1.001-1.026), vascular reconstruction (OR = 9.897, 95% CI 2.405-40.733), soft pancreatic texture (OR = 5.243, 95% CI 1.628-16.885), and a main pancreatic duct diameter ≤3 mm (OR = 3.462, 95% CI 1.049-11.423), all associated with unplanned reoperation within 30 days post-LPD (all P < 0.05). Conclusion Postoperative bleeding is the primary cause of unplanned reoperations after LPD. Independent risk factors, confirmed by multivariate analysis, include low pre-operative serum prealbumin, elevated CRP on POD-7, vascular reconstruction, soft pancreatic texture, and a main pancreatic duct diameter of ≤3 mm. Comprehensive peri-operative management focusing on these risk factors can reduce the likelihood of unplanned reoperations and improve patient outcomes.